Axitinib in combination with pembrolizumab in patients with advanced renal cell cancer: a non-randomised, open-label, dose-finding, and dose-expansion phase 1b trial. Issue 3 (March 2018) - Atkins, Michael B; Plimack, Elizabeth R; Puzanov, Igor; Fishman, Mayer N; McDermott, David F; Cho, Daniel C; Vaishampayan, Ulka; George, Saby; Olencki, Thomas E; Tarazi, Jamal C; Rosbrook, Brad; Fernandez, Kathrine C; et al.
Summary: Background: Previous studies combining PD-1 checkpoint inhibitors with tyrosine kinase inhibitors of the VEGF pathway have been characterised by excess toxicity, precluding further development. We hypothesised that axitinib, a more selective VEGF inhibitor than others previously tested, could be combined safely with pembrolizumab (anti-PD-1) and yield antitumour activity in patients with treatment-naive advanced renal cell carcinoma. Methods: In this ongoing, open-label, phase 1b study, which was done at ten centres in the USA, we enrolled patients aged 18 years or older who had advanced renal cell carcinoma (predominantly clear cell subtype) with their primary tumour resected, and at least one measureable lesion, Eastern Cooperative Oncology Group performance status 0–1, controlled hypertension, and no previous systemic therapy for renal cell carcinoma. Eligible patients received axitinib plus pembrolizumab in a dose-finding phase to estimate the maximum tolerated dose, and additional patients were enrolled into a dose-expansion phase to further establish safety and determine preliminary efficacy. Axitinib 5 mg was administered orally twice per day with pembrolizumab 2 mg/kg given intravenously every 3 weeks. We assessed safety in all patients who received at least one dose of axitinib or pembrolizumab; antitumour activity was assessed in all patients who received study treatment and had an adequate baseline tumour assessment. The primary endpoint was investigator-assessed dose-limiting toxicity during the first two cycles (6 weeks) to estimate the maximum tolerated dose and recommended phase 2 dose. This study is registered withClinicalTrials.gov, numberNCT02133742 . Findings: Between Sept 23, 2014, and March 25, 2015, we enrolled 11 patients with previously untreated advanced renal cell carcinoma to the dose-finding phase and between June 3, 2015, and Oct 13, 2015, we enrolled 41 patients to the dose-expansion phase. All 52 patients were analysed together. No unexpected toxicities were observed. Three dose-limiting toxicities were reported in the 11 patients treated during the 6-week observation period (dose-finding phase): one patient had a transient ischaemic attack and two patients were only able to complete less than 75% of the planned axitinib dose because of treatment-related toxicity. At the data cutoff date (March 31, 2017), 25 (48%) patients were still receiving study treatment. Grade 3 or worse treatment-related adverse events occurred in 34 (65%) patients; the most common included hypertension (n=12 [23%]), diarrhoea (n=5 [10%]), fatigue (n=5 [10%]), and increased alanine aminotransferase concentration (n=4 [8%]). The most common potentially immune-related adverse events (probably related to pembrolizumab) included diarrhoea (n=15 [29%]), increased alanine aminotransferase concentration (n=9 [17%]) or aspartate aminotransferase concentration (n=7 [13%]), hypothyroidism (n=7 [13%]), and fatigue (n=6 [12%]). 28 (54%) patients had treatment-related serious adverse events. At data cutoff, 38 (73%; 95% CI 59·0–84·4) patients achieved an objective response (complete or partial response). Interpretation: The treatment combination of axitinib plus pembrolizumab is tolerable and shows promising antitumour activity in patients with treatment-naive advanced renal cell carcinoma. Whether or not the combination works better than a sequence of VEGF pathway inhibition followed by an anti-PD-1 therapy awaits the completion of a phase 3 trial comparing axitinib plus pembrolizumab with sunitinib monotherapy (NCT02853331 ). Funding: Pfizer Inc.